General considerations about the use of the electrolarynx in a laryngectomized patient during voice therapy - Poblete S., Mariella (2012)
The aim of this paper is to spread the use of the electrolarynx as one of the methods used within the context of voice therapygiven to a person who has lost the larynx and therefore the ability to communicate orally, with the role of the voice pathologyspecialist being decisive the in improving the quality of life for cancer patients